Why People Are in a Generally Good Mood. (August 2015) - Diener, Ed; Kanazawa, Satoshi; Suh, Eunkook M.; Oishi, Shigehiro
Evidence shows that people feel mild positive moods when no strong emotional events are occurring, a phenomenon known as positive mood offset. We offer an evolutionary explanation of this characteristic, showing that it improves fertility, fecundity, and health, and abets other characteristics that were critical to reproductive success. We review research showing that positive mood offset is virtually universal in the nations of the world, even among people who live in extremely difficult circumstances. Positive moods increase the likelihood of the types of adaptive behaviors that likely characterized our Paleolithic ancestors, such as creativity, planning, mating, and sociality. Because of the ubiquity and apparent advantages of positive moods, it is a reasonable hypothesis that humans were selected for positivity offset in our evolutionary past. We outline additional evidence that is needed to help confirm that positive mood offset is an evolutionary adaptation in humans and we explore the research questions that the hypothesis generates.